Navicular tenosuspension with anterior tibialis tendon (Young procedure) associated to calcaneo-stop for the treatment of paediatric flexible flatfoot: clinical and ultrasound study - Samaila, Elena; Bonetti, Ingrid; Bruno, Costanza; Argentini, Emanuele; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: Flexible flatfoot is one of the most common deformities in pediatric orthopaedics. Arthroeresis procedures are designed to correct this deformity. Among them, calcaneo-stop is a procedure with both biomechanical and proprioceptive properties. There could be other surgical procedure combined, such as a percutaneous Achilles tendon lengthening and the Gould tibialis posterior retension or Young tibialis anterior navicular tenosuspension. This study analyzed the clinical and sonographic results of 36 patients following flexible flatfoot surgical treatment with a calcaneo-stop arthroeresis combined with Achilles lengthening and a Young procedure. Methods: From March 2001 to August 2014, 36 patients (54 feet) were treated with calcaneo-stop arthroeresis, percutaneous Achilles tendon lengthening and Young’s tenosuspension. The clinical assessment and a sonography of the anterior tibialis tendon (ATT) were performed in all patients. Results: The average follow-up was 7.4 years (range 8 months-14 years) with a satisfactory outcome in 51 feet (94.5%). No major and minor complications were observed. In four cases the calcaneo-stop was removed for pain and low tolerance of the patient. The AOFAS score and the talocalcaneal angle did not have statistically significant in case of ATT was or not still inserted in the navicular at the follow-up. Conclusions: The calcaneo-stop procedure is a simple, reliable and minimally invasive procedure for the treatment of pediatric flexible flatfoot. Although the indications for the Young tenosuspension as an isolated procedure is very narrow, it can still be an effective procedure when combined to calcaneo-stop. The key to appropriate utilization is a thorough understanding of the biomechanics of the foot function and a specific appreciation of the function of the ATT